Prevalence and recognition of highly significant medication-smoking cessation interactions in a smoke-free hospital. (1st July 2019) - Chui, Chang Yue; Taylor, Simone E.; Thomas, Dennis; George, Johnson
Highlights: The first study investigating the prevalence of medication-smoking cessation interactions. Highly significant medication interactions with smoking-cessation were prevalent. These interactions were overlooked by health professionals. Abstract: Background: Some medications are more rapidly metabolized by smokers; upon smoking cessation, medication metabolism may be significantly reduced, resulting in medication-related adverse events. Clozapine, olanzapine and theophylline have been deemed to have potentially highly significant interactions with smoking cessation, which could lead to seizures, extrapyramidal effects and tachycardia, respectively. This study examined the period prevalence and characteristics of patients at risk of highly significant medication-smoking cessation interactions when admitted to a smoke-free hospital. Methods: A retrospective cross-sectional study was undertaken in an Australian tertiary-referral hospital with a well-established electronic prescribing system. Smokers prescribed clozapine, olanzapine or theophylline prior to and during a hospital admission in 2015 were included. Length of hospital stay, daily doses, and recognition of the potential interaction by treating clinicians were determined from medical records. Results: The period prevalence of patients at risk of a potentially highly significant medication-smoking cessation interaction was 23/48 (48%), 66/256 (26%) and 1/16 (6%) amongst smokers prescribed clozapine, olanzapine or theophylline, respectively. These interactions were poorly recognized by healthcare professionals during the admission. Conclusions: Up to one in two patients receiving medications that have potentially highly significant interactions with smoking cessation may be experiencing clinically significant potential interactions. Such interactions, however, were commonly overlooked by hospital staff. Interventions to improve awareness of this issue are warranted.